Impact of developer–designer collaboration behaviour for ISD project success : A study in collaboration habits of two ISD project roles - Seppänen, Juha (My University, 2021)
Information systems development (ISD) has always been a complicated business, and it has been getting more complicated over time. Failure is still commonplace despite advances in project methodologies, techniques, and tools. In this thesis, two ISD roles, the designer and the developer, were studied. Seven inform- ants were interviewed — four designers and three developers. The research goal was to find out how the designers and the developers collaborated during the ISD project and what impact their collaborative effort may have on the result of the developed information system. The material was collected via interviews and in-situ observation of the workspaces. A semi-structured interview method was used where a set of structured interview questions was used as a basis for interview sessions but also let the discussion flow into directions where it was naturally heading. The interviews were transcribed and coded into the NVivo system by interview themes. Emergent themes were added during text analysis, and transcripts were analyzed again to en- sure the emerged themes could be analyzed as well. Observation notes were added to the set of codes and mixed with the interview data. According to the research results, an ISD's success depends on the fluent collaboration of the designer and the developer. Multiple factors were found that lower the risk of ISD failure. Even though their roles are somewhat indeterminate and vary slightly between different com- panies and teams, these two roles are essential for the success of an ISD project. The role of a customer emerged as the essential stakeholder during an ISD project. All informants mentioned that without clear lines of communications, commonly agreed on goals with milestones, and an overall common understanding of the IS to be developed, the likelihood of failure increases.

Tietojärjestelmäkehitys on aina ollut vaikeaa ja monimutkaista toimintaa, jossa ajan mittaan monimutkaisuus on muuttunut monelta osin kompleksisuudeksi. Epäonnistuneet tietojärjestelmähankkeet ovat edelleen tavallisia huolimatta hankehallinnan menetelmien, tekniikoiden ja työkalujen kehittymisestä. Tässä tutkielmassa tutkimuskohteeksi valittiin kaksi tietojärjestelmäkehityksen roolia: suunnittelija ja kehittäjä. Seitsemän vapaaehtoista ammattilaista valittiin haastatteluihin, joista neljä oli suunnittelijoita ja kolme kehittäjiä. Tutkimuksen tavoitteena oli saada ymmärrys, miten suunnittelijat ja kehittäjät toimivat tiiviisti yhdessä tietojärjestelmäkehitysprojektin aikana ja millainen vaikutus jos mitään heidän yhteistoimintansa laadulla on tietojärjestelmäprojektin onnistumiseen. Tutkimusmateriaali kerättiin seitsemän vapaaehtoisen ammattilaisen yksilöhaastattelulla. Tiedonkeruussa käytettiin teemahaastettelumenetelmää. Haastattelut litteroitiin ja koodattiin NVivo järjestelmään haastattelurungossa mainittuihin teemoihin. Uusien teemojen noustua esiin litteroinnit käytiin läpi uudestaan ja löytyneet koodit lisättiin. Työtilojen havainnoinnin muistiinpanot koodattiin yhdessä haastatteluissa esiin tulleiden kommenttien kanssa. Tutkimustulosten perusteella tietojärjestelmähankkeen menestys on jossain määrin riippuvaista suunnittelijoiden ja kehittäjien sujuvasta yhteistoiminnasta. Tuloksissa mainitaan useita tekijöitä, joiden huomioonottamisella riskiä voidaan tuntuvasti vähentää. Vaikka roolien määrittely ei ole selkeää voidaan silti sanoa, että tällä työparilla on usein ratkaiseva vaikutus tietojärjestelmähankkeen onnistumiseen. Tämän lisäksi asiakkaan rooli nousi esiin keskeisenä tekijänä suunnittelijoiden ja kehittäjien mielestä.
Keywords: developer, designer, collaboration, tools, roles, success, failure, ISD, SDLC